LATIN AND GREC TERMINOLOGY IN THE PROCESS OF STUDY OF OPERATIVE SURGERY (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
The article discusses the problem of the prevalence of foreign terms in the field of operative surgery. We reveal the definition of ways to replenish the vocabulary of the “medical” language. Expressions borrowed from other languages, such as Latin and Greek, are described.